A counterfeit betrothal/the notorious rake ebook Two novels in one volume. - Balogh, Mary (2013)
NEW YORK TIMES BESTSELLER Mary Balogh presents two of her classic Regency-era romances—seductive tales of ladies who are running away from love . . . and rogues who enjoy the chase.   A COUNTERFEIT BETROTHAL   Lady Sophia Bryant has no intention of marrying anytime soon. Her one desire is to reunite her parents, who have been estranged for fourteen years. Surely, if she happens to announce her betrothal—even a false one—they will be forced to see each other. Devilishly handsome Lord Francis Sutton seems perfect for such deceit, always agreeable to games of passion in which he has nothing to lose. The trap is set—if only Lady Sophia can keep her foolish heart from falling prey to her brilliant snares.   THE NOTORIOUS RAKE   Lord Edmund Waite is everything that Lady Mary Gregg despises: lewd, lascivious, mocking—the most incorrigible and successful rogue around. A bluestocking like her would never tempt a man whose taste runs to pretty playthings—so Mary is startled to find herself the object of Lord Edmund’s desires. Even more surprising is her reaction to his shocking advances. She may be a lady, but this man knows so well how to make her feel like a woman. Includes excerpts of  The Proposal and The Arrangement by Mary Balogh